The use of motion-tracking games for rehabilitation of the paretic upper extremity in individuals with stroke - Klinedinst, Tara, author; Malcolm, Matthew, advisor; Roll, Marla, committee member; Pasricha, Sudeep, committee member (Colorado State University. Libraries, 2015)
BACKGROUND: Every 45 seconds in the United States, someone experiences a stroke. Stroke is the leading cause of disability in the United States, which underscores the importance of access to efficacious and feasible rehabilitation treatment. Researchers have estimated that 77% of survivors experience upper extremity weakness, or paresis after stroke. When this weakness affects one side of the body, it is known as hemiparesis. Overall, a large volume of therapy is required to produce the neuroplastic changes that lead to meaningful recovery post-stroke, but with the constraints of conventional, "hands-on" approaches, a system is needed that allows for convenient, at-home practice with remote supervision and feedback of a therapist. Over the last 30 years, treatments have emerged through scientific advances, which integrate the principles provided by conventional therapy treatment using computer technology. These treatments allow for repetitive action-based, at-home practice. METHOD: Four participants who have experienced stroke were recruited from the northern Colorado community. The materials used for the study include the suite of web-based games, a commercially available Leap Motion sensor, a custom stand designed to hold the sensor, and a laptop computer. To use the game, participants moved their hand underneath the motion sensor which interacts with the games on the computer screen. The researchers adjusted the difficulty, time, and sensitivity of the games depending on the movement capacity of the participant. The intervention sessions took place over five consecutive days, except for one participant who used the system in his home over 10 consecutive weekdays. The participants were assessed using the Wolf Motor Function Test (WMFT), the Fugl-Meyer Assessment-Upper Extremity Test (FMA-UE), and the "Quality of Movement" scale of the Motor Activity Log (MAL-QOM). The baseline and post-intervention scores on the WFMT-Timed, the WMFT-FA, the MAL-QOM and the FMA were analyzed using Wilcoxon's Signed-Rank Test. RESULTS: The mean scores in all measures of motor performance moved in the direction of improvement, though none were shown to be statistically significant. The intervention was overall well-tolerated by the participants, with no adverse effects reported. DISCUSSION: The primary aims of the study were to investigate the efficacy and feasibility of an at-home, motion-tracking rehabilitation gaming system (GATOR) for increasing users' real-world use of their paretic upper extremity. Future research on this system with increased length of treatment in the home of the participant is needed to further evaluate the use of this system as a rehabilitation technology for the increased use of the stroke-affected arm.
Keywords: cerebrovascular accident; computer-based; motion-tracking; rehabilitation; stroke; upper extremity